A Review on Effect of Social Media on Education in Sudan - Hassan, Mohamed Ibrahim Alsaid; Kommers, Piet (International Journal of Educational Technology and Learning, 2018)
Social networking is one of the most important media outlets, whose stars have risen in cyberspace, becoming a prominent communication tool, particularly in students’ communities. Technology integration is being increasingly used in instruction to improve teaching and learning. In Sudan as a developing country, the extent to which educators are able to integrate social media into the curriculum is limited. There is no actual practice of ICT in the learning process, but use it as an additional use in the teaching process. New methods must be improved to integrate that into the curriculum. In this survey paper, past and recent related works are reviewed some investigated to use Social media by teachers in promoting the educational process.